Identification and Validation of the Immune Subtypes of Lung Adenocarcinoma: Implications for Immunotherapy - Song, Yang; Yan, Shi; Fan, Weina; Zhang, Mengyan; Liu, Wei; Lu, Hailing; Cao, Mengru; Hao, Chenguang; Chen, Lin; Tian, Fanglin; Zhan, Yuning; Cai, Li; et al. (Frontiers in Cell and Developmental Biology, 2020)
Lung adenocarcinoma (LUAD) is a devastating disease with poor patient survival. Cancer immunotherapy has revolutionized the treatment of LUAD, but only a limited number of patients effectively respond to this treatment. Thus, the work to elucidate the LUAD immune heterogeneity could be crucial in developing new immunotherapeutic strategies with better efficacy. This study Non-negative matrix factorization-based deconvolution was performed to identify robust clusters of 489 LUAD patients in The Cancer Genome Atlas (TCGA) and verify their reproducibility and stability in an independent LUAD cohort of 439 patients from the Gene Expression Omnibus (GEO). We used the graph learning-based dimensionality reduction to visualize the distribution of individual patients. In this study, 4 reproducible immune subtypes, Clusters 1-4 (C1-C4) associated with distinct gene module signatures, clinicopathological features, molecular and cellular characteristics were identified and validated. The immune-cold subtype, C3, was associated with the Dead event, the most advanced T stage, N stage, TNM stage and the worst prognosis for LUAD patients. Moreover, C3 also exhibited the lowest inﬁltrating levels of B cells and T cell receptor (TCR) repertoire diversity among C1-C4. On the other hand, the immune-hot subtype (C4) exhibited the highest infiltration of six types of infiltrating immune cells as well as the greatest leukocyte fraction, TCR and B cell receptor (BCR) repertoire diversity. C1 and C2 subtypes showed diverse clinicopathological and immunological features. Finally, our investigations discovered a complex immune landscape with a scattered immune subtype profile. This work may help inform immunotherapeutic decision-making and design advanced immunotherapy strategies for the treatment of lung cancer.